Development of a sun-shading louver unit with evaporative cooling effect. (28th May 2019) - He, Yuting; He, Jiang; Li, Yigang
Abstract : This study proposed a sun-shading louver unit with evaporative cooling. It has water sprayers and its louver boards were made of porous materials for absorbing spraying water. This article is focused on the structure of the louver unit and the operation mode of the water spraying system. The proportion of current windows is discussed in the first part, and solar radiation irradiated on the louver is used to calculate water evaporation from the cooling components mounted in the vertical plane. According to the evaporation time, the spraying operation time of the matching spraying system can be controlled to ensure the cooling louver has been in a wet state. This article also presents the improvement effect on the thermal environment using simulation results of indoor and outdoor environments. The operation modes of water spraying on the sun-shading louver with different orientations are also discussed. The simulation results show that mean radiant temperatures near the sun-shading louver are obviously lowered, and the heat island potential in the area with the louver is also decreased. Last, a case study was conducted for applying the louver unit to different environments in the hot summer and warm winter climates.